2017
DOI: 10.1093/cercor/bhw415
|View full text |Cite
|
Sign up to set email alerts
|

Fine Motor Skill Mediates Visual Memory Ability with Microstructural Neuro-correlates in Cerebellar Peduncles in Prematurely Born Adolescents

Abstract: Adolescents born preterm (PT) with no evidence of neonatal brain injury are at risk of deficits in visual memory and fine motor skills that diminish academic performance. The association between these deficits and white matter microstructure is relatively unexplored. We studied 190 PTs with no brain injury and 92 term controls at age 16 years. The Rey–Osterrieth Complex Figure Test (ROCF), the Beery visual-motor integration (VMI), and the Grooved Pegboard Test (GPT) were collected for all participants, while a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 55 publications
4
7
0
2
Order By: Relevance
“…These differences are of interest when considered in the context of the multiple prior investigations detailing prematurity-related reductions in cerebellar volumes and growth trajectories (Allin M et al 2001; Volpe JJ 2009; Bouyssi-Kobar M et al 2016). Prior work in VPT children has suggested stronger CB structural connectivity is linked with improved fine motor dexterity and visual-motor integration in adolescence (Thomas AR et al 2017), a finding consistent with the present functional connectivity results. Similarly, preterm children with diffuse PVL with lower GMFCS scores ( i.e.…”
Section: Discussionsupporting
confidence: 91%
“…These differences are of interest when considered in the context of the multiple prior investigations detailing prematurity-related reductions in cerebellar volumes and growth trajectories (Allin M et al 2001; Volpe JJ 2009; Bouyssi-Kobar M et al 2016). Prior work in VPT children has suggested stronger CB structural connectivity is linked with improved fine motor dexterity and visual-motor integration in adolescence (Thomas AR et al 2017), a finding consistent with the present functional connectivity results. Similarly, preterm children with diffuse PVL with lower GMFCS scores ( i.e.…”
Section: Discussionsupporting
confidence: 91%
“…A smaller precentral gyrus could, therefore, be expected to be correlated with reduced motor performance and also to diminished VMI performance, in line with our findings, since fine motor skills have been shown to be a mediator of visuomotor function, even though the cause of this mediation is not known. 47 Both the cerebellum and the brain stem are important for fine motor skills and VMI, as well as for other tasks that rely on the motor system, 48 and our results support their important role in this cross-modal function. In addition, the cerebellum has long been known to be involved in movement modulation, balance and coordination, and there is now evidence that it is also important for a number of cognitive functions, including visuospatial attention.…”
Section: Discussionsupporting
confidence: 73%
“…And, fine motor skills have been shown to be a facilitator of visuomotor function even though the causality of this mediation is not known. 47 The present study revealed positive correlations between better fine motor skills and larger volumes of the precentral gyrus, the cerebellum and the brainstem—motor areas of the brain that have been reported to be involved in fine motor skills. 50 The precentral gyrus, which is located in the frontal lobe, is the origin of the corticospinal tracts known to affect motor functions.…”
Section: Discussionsupporting
confidence: 63%
“…Fine motor skills have been reported to be indirectly linked to mathematics through VMI in term-born children (21). This was in line with a study of preterm born adolescents that showed that fine motor skills largely mediate VMI function (22). As children born EPT are more likely to be left-handed (23), we also wanted to explore if this affected their VMI performance.…”
Section: Discussionsupporting
confidence: 58%